Women's Experiences With Feelings and Attractions for Someone Outside their Primary Relationship. Issue 5 (3rd July 2016) - Mullinax, Margo; Barnhart, Katie Jo; Mark, Kristen; Herbenick, Debby
Abstract : The purpose of this article is to explore women's experiences with attractions and feelings for people outside their primary romantic relationship. In an anonymous Internet-based survey, 160 women answered open-ended questions about crushes. Women had varied experiences with, and diverse strategies for, managing crushes. The majority of women reported the crush did not impact their primary relationship; participants also reported that these crushes improved their desire for their partner. The majority of women in this sample did not communicate with their partners about their crushes. This research can be used by therapists and counselors working with patients experiencing these feelings.